Universal critical behavior in tensor models for four-dimensional quantum gravity - Eichhorn, Astrid; Lumma, Johannes; Duarte Pereira Junior, Antônio; Sikandar, Arslan (Journal of high energy physics, 2020)
Four-dimensional random geometries can be generated by statistical models with rank-4 tensors as random variables. These are dual to discrete building blocks of random geometries. We discover a potential candidate for a continuum limit in such a model by employing background-independent coarse-graining techniques where the tensor size serves as a pre-geometric notion of scale. A fixed point candidate which features two relevant directions is found. The possible relevance of this result in view of universal results for quantum gravity and a potential connection to the asymptotic-safety program is discussed.
Gesehen am 02.04.2020